Effect of pre-milking udder stimulation on milk parameters in crossbred cows - SHINDE, KULADIP PRAKASH (Indian Journal of Dairy Science, 2016)
The objective of this study was to find out the effect of pre-milking udder stimulation on milk parameters in crossbred cows. Eighteen apparently healthy cross bred cows were randomly selected and divided into three treatments groups (6 in each group) namely T1, T2 and T3 based on udder stimulation for one minute, two minutes and three minutes, respectively. Milk yield was significantly (p<0.05) higher in treatment group T2, fat (%) was significantly (p<0.05) higher in treatment groups (T1 &T3)and SNF (%) was significantly (p<0.05) higher in treatment groups T1 & T3. No, significant difference in acidity and specific gravity was observed among all the three groups. In treatment group T1, milk yield showed significant negative correlation (p<0.05) with SNF. Fat percentage showed significant positive correlation (p<0.05) with SNF and acidity. SNF was positively (p<0.01) correlated with acidity. In treatment group T2, milk yield showed significant negative correlation (p<0.05) with acidity. Fat percentage showed significant positive correlation (p<0.01) with acidity and significant negative correlation (p<0.05) with specific gravity. SNF was negatively correlated (p<0.05) with specific gravity. In treatment group T3, negative correlation (p<0.01) was observed between milk yield and fat percentage. Positive correlation (p<0.01) was observed between milk yield and SNF. Fat percentage was positively correlated (p<0.01) with specific gravity. Milk yield was better when udder was stimulated for two minutes before milking and fat and SNF percentage were better when udder was stimulated either for one minute or three minutes before milking.Â . For better milk yield, pre-milking udder stimulation for two minutes and for better of fat or SNF, it is better to stimulate udder for one minute.